Multiculturalism and social cohesion: A Japanese community's perceptions of "being Australian". Issue 1 (27th December 2020) - Funaki, Shinsuke; Hamano, Takeshi; Phillips, Ruth
Abstract: Based on a large‐scale survey conducted with parents from Japanese language schools in Sydney in 2015, this paper aims to review multiple dimensions of social cohesion in the Japanese ethnic community in Australia. Looking at several indices such as economic, political, and cultural integration, the paper describes the social profile of the Japanese ethnic community, questioning the generic perception of the community as a coherent body of middle‐class migrants in Australia. This was achieved through a comparative analysis with outcomes of a national survey of the Australian population on social cohesion and draws attention to the ways in which a particular sense of social cohesion with Australian society is constructed by Japanese migrants. The study found a differentiated sense of belonging to the local community, country of residence (Australia), and nation of origin (Japan). It found communal diversity in the Japanese community resulting from there being a majority of women migrants who were part of cross‐border marriages and their children living in multicultural family circumstances. It was concluded that this configuration within the community leads to advocacy related to a re‐identification as a possible ethnic group of migrants that should be recognized in an inclusive migration settlement policy in Australia.